Gottes Liebe zu Israel Studien zur Theologie des Alten Testaments - Spieckermann, Hermann 1950- (Tübingen Mohr Siebeck, 2004)
Den im vorliegenden Band zusammengestellten Studien ist die Frage nach Wesen und Wirken Gottes im Alten Testament gemeinsam. Ohne daß bei ihrer Abfassung die Absicht leitend gewesen wäre, ergibt sich aus ihnen im Rückblick ein zielgerichtetes Fragen nach Möglichkeit und Konzeption einer Theologie des Alten Testaments. In ihrem Zentrum wird Gottes Selbstbestimmung zur Liebe erkannt. Diese Liebe richtet sich zunächst auf sein Volk Israel, nimmt aber bald auch die Völkerwelt in den Blick. Die Liebesgeschichte Gottes mit seinem Volk und der Welt entfaltet sich zwischen spannungsvollen Polen. Sie ist zu keinem Zeitpunkt eine unproblematische Geschichte. Sie kennt keine Liebe ohne Untreue, keine Erfahrung der Nähe ohne die Ferne, aber auch keinen Zorn ohne Gnade. In zwölf Studien werden Szenen dieser Liebesgeschichte beleuchtet. In der zwölften wird der Aufriß des ganzen Heilsdramas erkennbar.»This beautifully produced volume contains twelve essays by the professor of Old Testament at the University of Göttingen. Eleven of the studies have been published previously and one appears for the first time in German. The leitmotif of the essays concerns the possibility and concept of a theology of the OT. ... This is an extremely useful collection which aptly displays S.'s breadth of knowledge and interest and the reader eagerly awaits S.'s OT theology as a whole.«A.C. Hagedorn in Book List 2002, S. 179f.
In his studies, Hermann Spieckermann deals with the question of the nature and the works of God in the Old Testament. Although when writing them this was not the author's primary intention, in retrospect they all turned out to focus on the question of the feasibility and the concept of a theology of the Old Testament. At the centre of this is the recognition of God's self-determination to love. In the beginning, this love is directed towards his people, the people of Israel, but it soon includes other nations as well.»This beautifully produced volume contains twelve essays by the professor of Old Testament at the University of Göttingen. Eleven of the studies have been published previously and one appears for the first time in German. The leitmotif of the essays concerns the possibility and concept of a theology of the OT. ... This is an extremely useful collection which aptly displays S.'s breadth of knowledge and interest and the reader eagerly awaits S.'s OT theology as a whole.«A.C. Hagedorn in Book List 2002, S. 179f.
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Forschungen zum Alten Testament; Studienliteratur; Israel; Altes Testament; Gott; Textbooks - Theology; Array; Studienliteratur - Theologie